Imitations - Ellis, S. (1999)
As many skaters do not have access to ice in the summer, they need to simulate the skating motions off ice to keep in shape. They do this through roller-skating, slide board, and imitations and jumps. These not only keep them in shape, but can be used to increase power, strength, local muscular endurance, and to correct errors made in technique during actual skating. There are three basic types of imitations skaters should learn straightforward low walk, side steps, and 45 steps. They are described here.